Pengaruh Keamanan, Pelayanan Sistem Online, Ketepatan Waktu Dan Tarif Terhadap Keputusan Pembelian Tiket Transportasi Kereta Api Tawang Alun PT. KAI (Persero) - Alan, Tri Setyo Budi; Rizal, Mohammad; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract punctuality and tariffs on purchasing decisions for train transportation tickets at PT. Kai (Persero) Tawang Alun. This study approach makes use of a quantitative approach. The people used is users of Tawang Alun train services and 110 respondents were obtained using Malhotra's theoryAn online questionnaire serves as a tool for gathering data. The data technique analysis analysis of multiple linear regression. used in conjunction with IBM SPSS Statistics 26. Hypothesis testing uses the F test and t test. According to this report, Security, Online System Services, Punctuality and Tariffs on Buying Choices together possess a substantial influence on purchasing decisions for Tawang Alun Train Transportation Tickets at PT. Kai (Persero). The variables Security, Online System Services, and Punctuality partially influence the purchasing decision for Tawang Alun Train Transportation Tickets at PT. Kai (Persero), while the Tariff variable does not have a significant influence.. Keywords : Security, Online System Services, Punctuality and Rates on Purchasing Decisions